The Effect Of The Development Of Maximum Oxygen Consumption In Football Players In The Recovery Of Basic Skills Acquired During Periods Of Muscle Fatigue Category Less Than 17 Years (an Experimental Study On The Teams Of The State Association Of The Mandate Of The Market For The Sports Season 2016/2017). - Khedri, Mohamedsalah; Khalfouni, Mohamed Adnan (Université de M'sila, 2019)
The objective of this research is to identify the relationship between one of the concerns of physiological characteristics of developing the maximum oxygen consumption and the extent of retrieval of the basic skills acquired in football for a class of less than 17 years during periods of muscle fatigue. To study the effectiveness of the development of maximum oxygen consumption, The study sample consisted of 38 randomly selected players, divided equally between two experimental and a witness groups. The researcher relied on the experimental method.. هدف هذا البحث الى التعرف على العلاقة الموجودة بين احد الهم الخصائص الفيسيولوجية و المتمثلة في تطوير الاستهلاك الأقصى للأكسجين و مدى إسترجاع المهارات الأساسية المكتسبة في كرة القدم لفئة اقل من 17 سنة خلال فترات التعب العضلي , و لدراسة مدى الفاعلية لتطوير الاستهلاك الأقصى للأكسجين ,قام الباحث بدراسة ميدانية على لاعبي فرق الرابطة الولائية لولاية سوق اهراس اقل من 17 سنة , حيث شملت عينة الدراسة على 38 لاعب اختارهم بطريقة عشوائية,مقسمة بالتساوي على مجموعتين تجريبية و شاهدة ,و قد اعتمد الباحث في هذه الدراسة على المنهج التجريبي.
Keywords: consommation maximale d'oxygène, compétences de base en football, fatigue musculaire, football. ; الاستهلاك الأقصى للأكسجين, المهارات الأساسية في كرة القدم ,التعب العضلي , كرة القدم.